2011
DOI: 10.1371/journal.pone.0027089
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in Body Ownership in Schizophrenia: Evidence from the Rubber Hand Illusion and Case Study of a Spontaneous Out-of-Body Experience

Abstract: BackgroundA weakened sense of self may contribute to psychotic experiences. Body ownership, one component of self-awareness, can be studied with the rubber hand illusion (RHI). Watching a rubber hand being stroked while one's unseen hand is stroked synchronously can lead to a sense of ownership over the rubber hand, a shift in perceived position of the real hand, and a limb-specific drop in stimulated hand temperature. We aimed to assess the RHI in schizophrenia using quantifiable measures: proprioceptive drif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
224
6
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(267 citation statements)
references
References 41 publications
25
224
6
5
Order By: Relevance
“…In addition, previous research has argued that drops in body / finger temperature can reflect a psychophysiological anxiety response (Vinkers, et al, 2013), and this has been shown for non-clinical samples in relation to body illusions (full body illusions: Salomon et al, 2013; the RHI: Moseley et al, 2008;Kammers et al, 2011;Thakkar et al, 2011: though see also Hohwy & Paton, 2010;Paton et al, 2012 for failures to replicate). Therefore, finger temperature was measured as an additional objective index of threat-related anxiety, via a separate channel on the same MP36R unit described above.…”
Section: Finger / Body Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous research has argued that drops in body / finger temperature can reflect a psychophysiological anxiety response (Vinkers, et al, 2013), and this has been shown for non-clinical samples in relation to body illusions (full body illusions: Salomon et al, 2013; the RHI: Moseley et al, 2008;Kammers et al, 2011;Thakkar et al, 2011: though see also Hohwy & Paton, 2010;Paton et al, 2012 for failures to replicate). Therefore, finger temperature was measured as an additional objective index of threat-related anxiety, via a separate channel on the same MP36R unit described above.…”
Section: Finger / Body Temperaturementioning
confidence: 99%
“…Research has argued that the hypothalamus and preoptic area (PO) play crucial roles in effective body temperature regulation, and a wealth of research has explored thermoregulation with respect to behaviour such as psychological reactivity to stress (Hammel, 1968;Nagashima, Nakai, Tanaka, & Kanosue, 2000;Oka, 2015;Oka, Oka & Hori, 2001). Indeed, drops in finger temperature have been associated with fear / anxiety responses (Vinkers et al, 2013), and have been demonstrated under body-illusion conditions (full body illusions: Salomon, Lim, Pfeiffer, Gassert & Blanke, 2013; the Rubber-hand illusion, RHI: Moseley et al, 2008;Kammers, Rose, & Haggard, 2011;Thakkar, Nichols, McIntosh, & Park, 2011: though see also Hohwy & Paton, 2010;Paton, Hohwy, & Enticott, 2012 for failures to replicate). This has led some researchers to suggest that such drops in temperature could also be used as a reliable index of fear processing, and that temperature regulation must therefore involve higher, top-down cognitive processing between physiological regulation of the physical self and the conscious 'self' (Moseley et al, 2008).…”
Section: Uncomfortably Numb 11mentioning
confidence: 99%
“…For example, the "rubber arm illusion", first introduced by Botvinick and Cohen in 1998 [3], pairs Virtual Blood Draw 4 tactile stimuli to one's actual arm with that observed on a rubber arm to induce a sense of "ownership" of the rubber arm. Drawing on recent research regarding optimal arm illusion parameters [3,5,20,34,36], the present study examined an extension of this approach by testing simulated ownership of a human arm depicted in virtual/digital format to facilitate exposure to a simulated blood draw. The blood draw procedure was selected due to its relevance to both blood and needles stimuli as well as syncopal response.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenic patients are found to have stronger experiences of the strange face illusion compared to healthy controls (Caputo et al, 2012). Individuals suffering from schizophrenia are also found to have deficits in self recognition (Irani et al, 2006;Platek & Gallup, 2002) and body/action awareness (Louzolo et al, 2015;Thakkar et al, 2011), but these unusual experiences are also not confined to mirror viewing, such that, similar to dysmorphic traits, delusions and schizophrenic/delusion symptoms may be related to usual experiences, but not specifically when looking in a mirror.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, schizophrenia as well as schizotypal traits are thought to be related to deficits in self-face recognition (Irani et al, 2006;Platek & Gallup, 2002) and body/action perception (Louzolo, Kalckert, & Petrovic, 2015;Thakkar, Nichols, McIntosh, & Park, 2011), which seems compatible with the experiences of strange face illusions. For many conditions in which self and body perception is impaired these experiences focus predominantly on the body rather than the face, yet, to date, whether perceptual illusions can occur when viewing our body rather than our face in the mirror has not been investigated.…”
Section: Introductionmentioning
confidence: 90%